Outpatient management practices associated with reduced risk of pediatric asthma hospitalization and emergency department visits - Lieu, T A; Quesenberry, Jr, C P; Capra, A M; Sorel, M E; Martin, K E; Mendoza, G R (Pediatrics (Evanston), 1997)
Effective outpatient care is believed to prevent hospitalization and emergency department (ED) visits resulting from childhood asthma. The aim of this study was to suggest priority areas for intervention by identifying outpatient management practices associated with the risk of these adverse outcomes in a large population. This case-control study included children aged 0 to 14 years with asthma who were members of a regional health maintenance organization. Cases were children undergoing either a hospitalization or an ED visit for asthma during the study period. Control subjects were children with asthma without a hospitalization or an ED visit during the study period who were matched to patients on age, gender, and number of asthma-related hospitalizations in the past 24 months. Data on provider and parent asthma management practices were collected using chart review, closed-ended telephone interviews with parents, and computerized use databases. Multivariate analyses were conducted using conditional logistic regression models. Data were collected on 508 cases and 990 control subjects. A total of 43% of cases were reported by their parents to have moderately severe or severe asthma, compared with 20% of control subjects. Parents of cases with hospitalization were less likely than control subjects to have a written asthma management plan (44% vs 51%) and to report washing bedsheets in hot water at least twice a month (77% vs 86%). Cases with hospitalization were more likely to have a nebulizer (74% vs 56%). In the final multivariate model, race/ethnicity was not associated with having had either a hospitalization or an ED visit, as was lower socioeconomic status. Having a written asthma management plan [odds ratio (OR): 0.54; 95% confidence interval (CI): 0.30, 0.99] and washing bedsheets in hot water at least twice a month (OR: 0.45; 95% CI: 0.21, 0.94) were associated with reduced odds of hospitalization. Having a written asthma management plan (OR: 0.45; 95% CI: 0.27, 0.76) and starting or increasing medications at the onset of a cold or flu were associated with reduced odds of making an ED visit. Practices that support early intervention for asthma flare-ups by parents at home, particularly written management plans, are strongly associated with reduced risk of adverse outcomes among children with asthma.